Clinical Usefulness of Contrast-Enhanced Computed Tomography in Patients with Non-Obstructive Acute Pyleonephritis - Sun, In O; Lim, Ji Hye; Oh, Ju Hwan; Cho, A Young; Kim, Beum Jin; Lee, Kwang Young; Lee, Mi Sook (Kosin Medical Journal (Online), 2020)
Objectives The aim of this study is to investigate the clinical utility of contrast-enhanced computed tomography (CE-CT) in patient with non-obstrcutive acute pyelonephritis (APN). Methods From 2007 to 2013, 537 APN patients who underwent a CE-CT scan within 24 hours after hospital admission were enrolled. We divided these patients into greater (50% or greater involvment, n = 143) and lesser (less than 50% involvement, n = 394) groups based on renal parenchymal involvement in CE-CT examination. We compared clinical characteristics between two groups and analyzed the clinical value of CE-CT scan as a reliable marker for predicting clinical severity and disease course in patient with non-obstructive APN. Results The mean estimated glomerular filtration rate was 70.6 ± 25.5 mL/min/1.73m2. Compared with patients in lesser group, the patients in greater group had lower serum albumin levels (3.5 ± 0.5 vs 3.8 ± 0.6, P < 0.01) and longer hosptal stay (10.1 ± 4.7 vs 8.8 ± 4.5, P < 0.05). In addition, acute kidney injury (AKI) (23.1% vs 11.4%, P < 0.005) and bacteremia (36.4% vs 26.8%, P = 0.02) were frequently developed in greater group, respectively. The overall incidence of AKI was 14.8% based on RIFLE criteria. In a multivariate logistic regression analysis for predciting AKI, age, presence of diabetes mellitus and the presence of renal parenchymal involvement of greater than 50% in CE-CT were significant predictors of AKI. Conclusions The CE-CT scan could be useful to predict the clinical severity and course in non-obstructive APN patients with preserved renal function.